2007
DOI: 10.1038/sj.bjc.6603944
|View full text |Cite
|
Sign up to set email alerts
|

MUC-1 gene is associated with prostate cancer death: a 20-year follow-up of a population-based study in Sweden

Abstract: Anti-adhesion mucins have proven to play an important part in the biology of several types of cancer. Therefore, we test the hypothesis that altered expression of MUC-1 is associated with prostate cancer progression. We retrieved archival tumour tissue from a population-based cohort of 195 men with localised prostate cancer (T1a-b, Nx, M0) that has been followed for up to 20 years with watchful waiting. Semi-automated, quantitative immunohistochemistry was undertaken to evaluate MUC-1 expression. We modelled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
(17 reference statements)
1
28
0
Order By: Relevance
“…High risk cancers generally had higher serum PSA concentrations, higher proportions of cores with cancer, higher median cancer length per core, and more adverse Gleason variables than not high-risk cancers ( Table 2). MUC1 expression was more frequent and ZAG staining less frequent in the biopsies from high-risk cancers compared with those not high-risk, consistent with the known biology of these proteins in prostate cancer [10,12,[30][31][32][33]. In those biopsies with >40% MUC1 staining, the associated RPx specimens had a much higher percentage of pattern 4 histopathology than in those without biopsy MUC1 expression (median 70% versus 20%, p<0.001, Wilcoxon rank-sum test).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…High risk cancers generally had higher serum PSA concentrations, higher proportions of cores with cancer, higher median cancer length per core, and more adverse Gleason variables than not high-risk cancers ( Table 2). MUC1 expression was more frequent and ZAG staining less frequent in the biopsies from high-risk cancers compared with those not high-risk, consistent with the known biology of these proteins in prostate cancer [10,12,[30][31][32][33]. In those biopsies with >40% MUC1 staining, the associated RPx specimens had a much higher percentage of pattern 4 histopathology than in those without biopsy MUC1 expression (median 70% versus 20%, p<0.001, Wilcoxon rank-sum test).…”
Section: Resultssupporting
confidence: 57%
“…Prior studies of RPx tissue have shown positive MUC1 or ZAG expression to be predictive of PSA failure and/or metastases, [10,12,[30][31][32][33] but no studies have investigated these markers in prostate biopsies, although Gunia et al showed that MUC1 expression in transurethral resection specimens ("incidental prostate cancers") predicted adverse pathology following subsequent radical prostatectomy [41]. The failure of our study to document a predictive capacity of MUC1 expression is most likely related to the small sample size (as relatively few biopsies stained MUC1 positive, the study lacked power to assess this biomarker), although it is also possible that its expression in biopsies is not strongly related to RPx pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies that have analyzed prediction of PCa-specific death, 39,46 -51 and even fewer have attempted to identify biomarkers of PCa-specific death. [52][53][54][55] The study reported here was possible because of our unique resources, including a large tissue bank and database with extensive follow-up clinical data for Ͼ15 years. Unlike most other cancers, PCa-specific death continues up to the 20th year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical intensity levels ranged from 0 to 255 chromogen intensity units. The correlation coefficient for the ASCIS II was r 2 = 0.973, and the reproducibility for the system was previously tested and confirmed by scoring several tissue microarrays on separate occasions and in previous publications (33,34).…”
Section: Pathologic Analysismentioning
confidence: 98%